Comparison of the Effects of Hysteroscopic Cold Broad Sword Play Combined with Estrogen and Progestin Sequential Therapy and Drospirenone and Ethinylestradiol Tablets in Patients with Severe Intrauterine Adhesion - Liping Zhou; Liqin Zhou; Tingting Wang (Emergency Medicine International)
Objective. To compare the effects of hysteroscopic cold broad sword play combined with estrogen and progestin sequential therapy and drospirenone and ethinylestradiol tablets in patients with severe intrauterine adhesion. Methods. One hundred and eight patients with severe IUA admitted to our hospital from May 2019 to October 2021 were selected for the study. Patients were divided according to their treatment regimen into group A (n = 54) treated with hysteroscopic cold broad sword play + drospirenone and ethinylestradiol tablets and group B (n = 54) treated with hysteroscopic cold broad sword play + estrogen and progestin sequential therapy. The two groups were compared in terms of perioperative indicators, recovery of uterine cavity status, inflammatory factor (C-reactive protein (CRP), interleukin 6 (IL-6), and interleukin 8 (IL-8)] levels), World Health Organization Quality of Life Brief Scale (WHOQOL-BREF) score, and clinical outcome at 3 months postoperatively. Result. After surgery, the duration of abdominal pain and vaginal bleeding was shorter in group A than in group B (P<0.05). After surgery, the time of menstruation return was shorter in group A than in group B, and the menstrual flow score was higher than in group B (P<0.05). At 3 months after the surgery, the uterine blood flow index, endometrial thickness, and uterine cavity volume were higher in group A than in group B, and the number of uterine readhesion was lower than in group B (P<0.05). 3 months after the surgery, the CRP, IL-6, and IL-8 levels decreased in both groups and were lower in group A than in group B (P<0.05). At 3 months after the surgery, the WHOQOL-BREF scores for each indicator were higher in both groups than before surgery and were higher in group A than in group B (P<0.05). At 3 months after the surgery, the overall valid rate of group A was 94.44% better than that of group B at 79.63% (P<0.05). Conclusion. The combination of hysteroscopic cold broad sword play with drospirenone and ethinylestradiol tablets has been shown to be more effective than combined estrogen and progestin sequential therapy in the treatment of patients with severe IUA, which significantly improves the post-operative menstrual status and uterine cavity morphology, significantly reduces the level of inflammatory factors in the patient’s body, and significantly improves the quality of life, which is of value.